Self Adjusment of Early Adult Single Mothers in Sub-District Dua Koto, Pasaman District and its Implication for Guidance and Counseling Services - Khairani Syafitri; Indah Sukmawati; Zadrian Ardi (Universitas Negeri Padang, 2020)
Adaptability is person’s ability to intereact with the environment naturally. In this study, a single mother with an age range of 18 to 40 years will be examined who was abandoned due to a divorce. This study aims to describe a single mother’s adjustment in general emotional maturity and social maturity. This research uses descriptive quantitative method. The subjects of this study were 32 single mothers in the Dua Koto sub-district, Pasaman district. The instrument used in this study was a questionnaire in the form of a likert scale. Research findings reveal that single mother adjusment is generally in the moderate category with a percentage of 81%. In particular, single mother adjusment from the aspect of emotional is in the medium category with a percentage of 96,88%. Aspect of social maturity are in the medium category with a percentage of 75%.